Constructivist strategy for health science education - H. C. Klopper (AOSIS, 2002)
The aim of this paper was to explore and describe a constructivist strategy for Health Science Educators. Changes in the higher education field in South Africa have impacted on the practice of health science educators. In the past, health science educators often envisaged their teaching task as  the transmission of content. This however no longer meets the needs of our practices.  In order to describe the strategy, the survey list of Dickoff, James and Wiedenbach (1968) was used to identify the core concepts. Each of the identified concepts was then described based on a literature review. The strategy advocates that health science  educators should shift from being lecturers to being learning facilitators based on the principles of constructivist learning, in order to create a context conducive to learning.